Papyri in the Princeton University Collections, Volume III : Taxation in Egypt from Augustus to Diocletian - Goodrich, Sidney Pullman, 1905-; Johnson, Allan Chester, 1881-1955 (Princeton legacy library., 2018)
Ninety-two documents of varied interest, all throwing light on the social and economic conditions of Roman Egypt. Each text is provided with ample commentary and critical notes.